Medical residencies for foreign Latin American graduated physicians in different countries - Bermeo Jaya, Hosny Kaddaffy (2024)
Medical residency is one of the alternatives that physicians from Latin American countries may decide to take at the end of their undergraduate studies. Many of them migrate due to socioeconomic situations and lack of opportunities in their countries of origin. Migration takes place to countries in different regions where eligibility methods, selection criteria, available medical specialties, remuneration systems and accrual differ. In the countries analyzed in this article, most of them have qualifying examinations for the practice of medicine and systems of financial compensation for the resident physician. The selection criteria vary from national examinations, matching systems and institutional evaluations and/or interviews.